Vapor adsorption limitation of graphene nanoribbons in quasi conductance increment: a NEGF approach - Shakil, Shifur Rahman; Zohra, Fatema Tuz; Pramanik, Parna; Tushar, Raihanul Islam; Saha, Atanu Kumar; Bhuian, Md Belal Hossain (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 10th IEEE International Conference on Nano/Micro Engineered and Molecular Systems, NEMS 2015; Xi'an; China; 7 April 2015 through 11 April 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/NEMS.2015.7147445